B7-H3-targeted CAR T cell activity is enhanced by radiotherapy in solid cancers - Ventin, Marco; Cattaneo, Giulia; Maggs, Luke; Jia, Jingyu; Arya, Shahrzad; Ferrone, Soldano; Wang, Xinhui; Ferrone, Cristina R. (Frontiers in Oncology, 2023)
Adoptive cell therapy utilizing T cells genetically modified to express a chimeric antigen receptor (CAR) has demonstrated promising clinical results in hematological malignancies. However, solid cancers have not seen a similar success due to multiple obstacles. Investigating these escape mechanisms and designing strategies to counteract such limitations is crucial and timely. Growing evidence in the literature supports the hypothesis that radiotherapy has the potential to enhance the susceptibility of solid tumors to CAR T cell therapy, by overcoming mechanisms of resistance. Radiation treatment can increase the susceptibility of different types of solid cancers (TNBC, HNSCC, PDAC) to B7-H3 CAR T cell-mediated eradication. Multiple mechanisms, including reduced cancer cell proliferation, upregulation of the targeted antigen, modulation of apoptotic molecules may contribute to this signal. The information in the literature and the results we describe support the ability of radiotherapy to improve the efficacy of CAR T cell therapy in solid tumors.